Comparison of MR Ultrashort Echo Time and Optimized 3D‐Multiecho In‐Phase Sequence to Computed Tomography for Assessment of the Osseous Craniocervical Junction. Issue 4 (26th December 2020) - Deininger‐Czermak, Eva; Villefort, Christina; von Knebel Doeberitz, Nikolaus; Franckenberg, Sabine; Kälin, Pascal; Kenkel, David; Gascho, Dominic; Piccirelli, Marco; Finkenstaedt, Tim; Thali, Michael J.; Guggenberger, Roman
Abstract : Background: To assess changes of the craniocervical junction (CCJ), computed tomography (CT) is considered the reference standard. Recent advances in bone depiction on magnetic resonance imaging (MRI) enable high‐quality visualization of osseous structures. Consequently, MRI may serve as an alternative to CT, without the use of ionizing radiation. Purpose: To compare two MRI sequences optimized for bone visualization to the CT reference standard in the assessment of the osseous CCJ. Study Type: Prospective. Population/Subjects: Twenty‐seven decedents and five healthy volunteers. Field Strength/Sequence: 3T/ultrashort‐echo time gradient echo (UTE) and optimized 3D‐multiecho in‐phase gradient echo sequences (FRACTURE). Assessment: All decedents were scanned with both MRI sequences and CT. Three observers rated degeneration to obtain a score for the upper (atlanto‐dental and left/right atlanto‐occipital joint) and for the lower part of the CCJ (left and right atlanto‐axial joint). Two reader rated the following quantitative parameters: basion‐axial‐interval, atlanto‐dental‐interval, atlanto‐occipital‐interval, Powers‐ratio, and signal/contrast‐to‐noise‐ratio. As a proof of concept, five healthy volunteers were scanned with both MRI sequences. Statistical Tests: Degeneration was assessed on a Likert scale by three independent observers. Interrater and intermodality reliability were calculated using an intraclass correlation coefficient. To compare distance measurements between examination methods, a Friedman test, between‐degenerative ratings, and a Kruskal–Wallis test were performed. Results: Degenerative ratings of the CCJ between MRI sequences and CT showed a good interrater and intermodality agreement. MRI sequences tended to underestimate the degree of degeneration compared to CT, and this became more marked with increasing degeneration severity. There were no significant relationships between distance measurements and the degree of degeneration ( P CT = 0.62, P UTE = 0.64, P FRACTURE = 0.67). The in vivo examination proved the feasibility of both MRI methods in a clinical setting. Data Conclusion: Quantitative and qualitative ratings on MR images were comparable to CT images; thus, MRI may be a valid alternative to CT assessing the CCJ. Level of Evidence: 1. Technical Efficacy Stage: 3.